Syngas production by catalytic in-situ steam co-gasification of wet sewage sludge and pine sawdust. (1st March 2016) - Hu, Mian; Gao, Lan; Chen, Zhihua; Ma, Caifeng; Zhou, Yan; Chen, Jian; Ma, Shu; Laghari, Mahmood; Xiao, Bo; Zhang, Beiping; Guo, Dabin
Highlights: Catalytic in-situ co-gasification of wet sewage sludge and sawdust was studied. NiO/MD catalysts showed a good performance on gasification process. A process to produce syngas by direct catalytic co-gasification of WSS and PS was proposed. Abstract: The catalytic in-situ co-gasification of wet sewage sludge (WSS) and pine sawdust (PS) for syngas production was studied. The thermogravimetric analysis showed that weight loss and the maximum weight loss rate of the sample increased with the increasing of PS content and the co-gasification behavior has obvious synergistic or coupling effects. The in-situ co-gasification process was performed in a lab-scale reactor to investigate the influences of PS content, catalyst and catalytic temperature on product yields, gas composition and gasification performances. The results indicated that the maximum dry gas yield (1.23 N m 3 /kg), H2 yield (14.44 mol/kg) and carbon conversion efficiency (84.56%) were obtained in presence of NiO/MD catalyst with 40% PS content in the blends and 900 °C catalytic temperature. The proposed direct catalytic co-gasification of wet sewage sludge and pine sawdust process may be a promising way to produce syngas using WSS.